Impact of exposure to brine/CO2 on the mechanical and transport properties of the Mt. Simon Sandstone. Issue 5 (19th August 2021) - Sun, Lin; Jessen, Kristian; Tsotsis, Theodore T.
Abstract: When sandstone rocks are exposed to CO2 ‐saturated brine, their transport and mechanical properties can, potentially, change due to chemical reactions as a result of such exposure. This paper investigates changes in the flow‐through characteristics, porosity, and the mechanical properties of Mt. Simon Sandstone samples caused by such exposure to brine/CO2 . A core, extracted from the Mt. Simon formation, was first characterized for its porosity and relevant transport properties, and it was then aged for over 500 hr in CO2 ‐saturated brine at formation‐relevant pressure, temperature, and confining stress conditions. The deformation of the sample was measured in situ during aging via strain gauges attached to the core's surface. Following the aging experiment, the sample's porosity and transport properties were again analyzed. Our experiments show that both the porosity and permeability of the Mt. Simon sandstone sample increase due to exposure to brine/CO2, with the impact on permeability being more significant. The deformation measurements employing strain gauges indicate a weakening of the core material. Analysis of the composition of the brine at the conclusion of the testing reveals changes, specifically, an increase in the concentration of several of the cations. These changes are indicative of mineral/clay dissolution, consistent with the porosity, permeability, and strain gauge measurements. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.